A Survey of Road Accident Reporting and Driver’s Behavior Awareness Systems: The Case of Tanzania - Mrema, I. J.; Dida, M. A. (Engineering, Technology & Applied Science Research, 2020)
Road traffic accidents are a leading cause of death in developed and developing countries. It has been shown that road accident reporting systems could reduce their effects by minimizing response time and mapping road accident-prone areas. This paper provides an overview of the systems and applications for road accident reporting and drivers’ behavior awareness. A field survey, conducted in Dar es Salaam region in Tanzania, investigated the current state of road traffic accident reporting. Findings showed that the main means of reporting road accidents were physical reporting and police emergency phone calls. The absence of alternative means for reporting road accidents causes information delay and lack of precise accident location for the emergency first responders. This paper concludes by proposing a mobile application system for road accident reporting and drivers’ over-speed awareness, in order to improve road safety in developing countries.